PERTIMBANGAN MAHKAMAH KONSTITUSI TERHADAP PUTUSAN NOMOR 22/PUU-XV/2017 TENTANG BATAS USIA MINIMAL MENIKAH BAGI PEREMPUAN PERSPEKTIF MAQĀSID SHARĪ’AH JASSER AUDA - Achmad Fauzan (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2019)
This article examines the legal reasoning of judges in the judicial review decision of Article 7 paragraphs (1) and (2) of Law No. 1 of 1974 on Marriage, which was submitted by applicants who were victims of underage marriage (below 16 years old). The main issue raised by the applicants was that Article 7 paragraphs (1) and (2) of Law No. 1 of 1974 were considered to contain elements of discrimination against women and were inconsistent with the 1945 Constitution, thus justifying the increase of the minimum marriage age. The Constitutional Court accepted the petition through Decision No. 22/PUU-XV/2017. Based on this background, the main focus of this study is to analyze the perspective of Maqāṣid al-Sharī‘ah on the legal considerations underlying this decision. This research is a library-based study, with primary data in the form of Constitutional Court Decision No. 22/PUU-XV/2017. Secondary data consist of relevant literature such as books, journal articles, newspapers, and other supporting documents. The data are analyzed using Jasser ‘Auda’s Maqāṣid al-Sharī‘ah framework with an inductive–deductive method. The approach applied in this study is juridical-philosophical. The results of the analysis indicate that the legal considerations of the Constitutional Court’s decision are in accordance with Jasser ‘Auda’s Maqāṣid al-Sharī‘ah. This is reflected through the application of the six system-based dimensions of maqāṣid: cognitive nature, wholeness (al-kulliyyah), openness, interrelated hierarchy, multidimensionality, and purposefulness.